Benarkah kader sebagai penentu kinerja posyandu? analisis 638 posyandu di IFLS 2014 (Berita Kedokteran Masyarakat (BKM), 2018)
Purpose: This study wanted to reveal who is determining the performance of integrated health post: cadres or officers who came to the community health centers of the population?. Method: This analysis uses data collected by 638 integrated health post of IFLS 2014 in 13 provinces of Indonesia. Results: Most of the services a child's weight and supplementary feeding (including vitamin A) is a hallmark of integrated health post. However, about 30-40% are not able to provide services integrated health post examination of pregnant women, iron services, oral rehydration salts, mild treatment, as well as maternal and child health. For services that are still lacking, the integrated health post with a more active cadres did not give any essential service. Conversely, the presence of public health center officers in integrated health post more determining the performance of critical services in integrated health post such as maternal and child health, the provision of oral rehydration salts, light treatment, the addition of iron, and prenatal care.Conclusion: Presence of cadres in integrated health post not specify of integrated health post performance. Instead, different from expectations, the presence of officers from the clinic specify the services that are important in integrated health post. Efforts to build the cadre system is more appropriate and relevant to the development of public health problems in the community of residents is our challenge.